Thermo-magnetic convection in a circular annulus filled with magnetocaloric nanofluid. (July 2020) - Dalvi, Shubham; Karaliolios, E.C.J.; van der Meer, Theo H.; Shahi, M.
Abstract: The present work is an effort to find a feasible design proposal which can ensure the continuous flow and self-sustained heat transfer within a circular annulus, solely because of magnetic forces. The objective is to study the change in flow characteristics because of magnetocaloric response of the nanoparticles used. In the present work, Mean Field Theory is used to calculate the specific magnetization and an improved viscosity model is used for considering its dependency on applied magnetic field. For better accuracy, individual mechanisms are considered while calculating the specific heat of magnetocaloric material. To have a better understanding, three different values of the remanent flux density ( Br ) and three distinct geometrical configurations are compared for their flow and thermal characteristics. For all cases, a periodic clockwise rotation of the fluid is observed and it is noticed that, the frequency of this rotation varies with both geometrical dimensions and Br . The main purpose of the current analysis is to contribute the preliminary data, which will further enhance our understanding about applications of Thermo-Magnetic Convection and Magnetocaloric Effect in heat transport devices.